Comparison of Early Outcome of Off-pump and Conventional Coronary Artery Bypass Graft Surgery in Patients with Left Main Coronary Artery Disease with Left Ventricular Dysfunction (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Left Main (LM) coronary artery disease and left ventricular dysfunction both are important predictors of in-hospital mortality. To avoid the harmful effects of cardio pulmonary bypass (CPB), many cardiac surgeons are using Offpump Coronary Artery Bypass (OPCAB) as an effective alternative to conventional CABG (CCAB) even in these sub-groups of patients. This study performed in the National Institute of Cardiovascular Diseases (NICVD) evaluated the early outcomes of OPCAB in terms of mortality and major post-operative morbidities and compared them with that of CCAB in patients with left main coronary artery diseases with left ventricular (LV) dysfunction. Total 120 patients with left main coronary artery disease with reduced left ventricular ejection fraction (